Social workers' knowledge and skills and the Care Act: Practice Advice Note - Jenkinson, Angela; Chamberlain, John (King's College London, 2019)
The need for a practice advice note on the roles of social workers in the Care Act was identified by the Chief Social Worker and was reinforced by a consultation with 140 social workers, who agreed the general content of this advice.
The Advice Note identifies social workers as being fundamental to the achievability of the Care Act because they are registered as having the knowledge and skills to achieve changes to protect, safeguard, promote and prioritise the well-being of individuals.
The Advice Note addresses the two distinct roles for social workers in the Care Act. The first is to provide counselling and other types of social work as a way of meeting needs. The second is to carry out assessments and make safeguarding decisions when there is a risk of harm to the individual were these to be carried out or made by a person who is not appropriately trained and does not have the relevant skills, knowledge and competence.
Twelve common misconceptions related to these roles are identified and are corrected by the relevant provisions in the Care Act.